Two-Dimensional Transient Finite Volume Difusional Approach to Transport Equations - da CUNHA, A.S.; FERREIRA, W.R. (Trends in Computational and Applied Mathematics, 2002)
This paper aims at presenting the Diusional Method coupled with the Finite Volume scheme as an alternative approach for solving convection-diusion equations, which under high Peclet numbers may congure a hard numerical task. It is also intended to test the proposed methodology for a case where analytical solution is known and for another one characterized by a high gradient prole. For the last case, results show that false diusion eects are present. Comparisons of the Diusional Method with other numerical schemes are also presented.